Analysis on the impact of renewable energy to power supply reliability - Kavhitra A/p V. Rajasekaran (2023)
In this paper, the impact of renewable energy is proposed on power supply reliability of power system network. Power supply reliability must always be in balance. Reliability can be analyzed as adequacy indicating that generation capacity always exists to cover power supply. Therefore, the solar energy is used in this research. Solar energy is an intermittent source of energy as it’s largely dependent in the environmental conditions. The impact of solar energy is due to its variation. Therefore, in this paper the impact of Photovoltaic (PV) integration in 39 bus test system is studied. The Siemens PSS/E (Power System Simulator for Engineers) software have been used to modeled PV plants. The PV are integrated at suitable locations to study the impacts of PV integration. The dynamic model is used from the PSS/E library. Furthermore, The PV integration capacity is determined based on the variation in slack bus with an increasing penetration of PV power. The simulation obtained from these studies indicate that PV plants aids to the reliability of the 39-bus test system.